The Effect of Customer Experience and Live Music Event Promotion on Bajawa Consumer Loyalty - Lim, Yudhi; Winarko, Hilarius Bambang; Panjaitan, Tetti Nauli; Rockiano, Sharon Octaviandre (Journal La Sociale, 2025)
Bajawa Café, which carries the theme of an ethnic modern coffee shop, is a café that highlights the culture of NTT (East Nusa Tenggara) and introduces it to urban communities in Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi). The café’s ambiance is traditional, with a strong Flores cultural nuance. This study aims to measure the influence of customer experience and live music event promotion on consumer loyalty at Bajawa Flores Café as an ethnic brand. The literature review of this research refers to the Elaboration Likelihood Theory (ELT). A sociopsychological research tradition is employed in this study. This research uses a descriptive approach with quantitative methods. The basic assumption of ELT is the study of persuasion, as it predicts when and how a person may or may not change their opinion (be persuaded) by a message or argument they receive. This study adopts a positivist paradigm to describe and explain social life, events, and human behavior. The research was conducted by visiting Bajawa Café to observe firsthand the cultural elements embedded in its exterior and interior, such as symbols, images, merchandise, entertainment offerings, and other aspects discovered during the visit. Questionnaires were distributed as primary data sources. Secondary data for this research included literature studies from books, scientific journals, online news articles, and verified internet sources. This study is expected to contribute to the development of marketing communication strategies that blend modern and traditional themes by measuring the influence of customer experience and live music event promotion on consumer loyalty at Bajawa Flores Café as an ethnic brand.